Analisis Pemahaman Mahasiswa Tentang Konsep Fisiologi Manusia dalam Pendidikan Ilmu Biomedis Dasar - Asih Luklu Susiati; Hardianto Hardianto; Ambo Anto; Zainul Muttaqin (Nursing Current: Jurnal Keperawatan, 2025)
Human physiology is a core subject in nursing education, providing essential knowledge for understanding the human body and applying this knowledge in clinical practice. Despite its importance, many nursing students face difficulties in mastering complex physiological concepts, leading to gaps between theoretical knowledge and practical application. Addressing these challenges is crucial to ensure that future nurses are adequately prepared to deliver safe and effective patient care. This study aimed to evaluate nursing students’ understanding of human physiology concepts in basic biomedical science education and to explore differences based on gender and semester level. A descriptive cross-sectional design was conducted with 50 nursing students from the second and fourth semesters at Famika University. Data were collected using a validated 25-item multiple-choice physiology test. Content validity was reviewed by experts, and a pilot test yielded a Cronbach’s alpha of 0.82, confirming good reliability. Data were analyzed using SPSS version 26 with descriptive statistics, independent t-tests, and chi-square tests, applying a significance level of p < 0.05. The results showed that second-semester students achieved higher comprehension scores (77.75%, Good) than fourth-semester students (68%, Fair). Male students also performed better (81.25%, Good) compared to female students (74.52%, Fair). These findings suggest that variations in students’ understanding may be influenced by academic workload, prior learning experiences, and learning motivation. Strengthening physiology education through active learning strategies and better integration of biomedical science content into the nursing curriculum is therefore recommended.